Plant Regeneration of Black Pepper (Piper nigrum L.) Through Meristem Culture - Rahman, M Ataur; Joarder, OI; Khondoker, IA; Paul, NK (Bangladesh Journal of Genetics and Biotechnology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Keywords: Black pepper; meristem culture; Piper nigrum; shoot regeneration; root induction Bangladesh j. genet. biotechnol. 7 (1&2): 91-93, 2006 (June & December)